2015
DOI: 10.1001/jama.2015.8761
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Clinical Studies Conducted Over the Total Product Life Cycle of High-Risk Therapeutic Medical Devices Receiving FDA Premarket Approval in 2010 and 2011

Abstract: Administration (FDA) approves high-risk medical devices, those that support or sustain human life or present potential unreasonable risk to patients, via the Premarket Approval (PMA) pathway. The generation of clinical evidence to understand device safety and effectiveness is shifting from predominantly premarket to continual study throughout the total product life cycle.OBJECTIVE To characterize the clinical evidence generated for high-risk therapeutic devices over the total product life cycle. DESIGN AND SET… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
116
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 94 publications
(117 citation statements)
references
References 24 publications
0
116
1
Order By: Relevance
“…Our findings are consistent with previous studies showing that even postapproval studies required by the FDA to be conducted by manufacturers are not always performed in a timely manner [13][14][15] and with previous work demonstrating the variability in the number and completion of postmarketing studies of high risk medical devices. 25 The majority of the postapproval studies that we identified focused on surrogate markers of disease. Using surrogate markers instead of clinical outcomes for trial endpoints has become increasingly controversial, 26 with several approved drugs ultimately failing to confirm any clinical benefit [27][28][29] and an analysis of oncology surrogate markers finding variable correlation with overall survival.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings are consistent with previous studies showing that even postapproval studies required by the FDA to be conducted by manufacturers are not always performed in a timely manner [13][14][15] and with previous work demonstrating the variability in the number and completion of postmarketing studies of high risk medical devices. 25 The majority of the postapproval studies that we identified focused on surrogate markers of disease. Using surrogate markers instead of clinical outcomes for trial endpoints has become increasingly controversial, 26 with several approved drugs ultimately failing to confirm any clinical benefit [27][28][29] and an analysis of oncology surrogate markers finding variable correlation with overall survival.…”
Section: Discussionmentioning
confidence: 99%
“…The FDA requires one pivotal and one non pivotal study for device approval, at minimum. A recent review of clinical trials found that the majority of devices have been approved with these minimal requirements, though some companies have ongoing studies throughout the device lifespan [7]. Regulatory bodies are left with the burden of navigating grey areas in approval and current accepted "best practices" in clinical trials.…”
mentioning
confidence: 99%
“…Literature can be found on recommendations, with some suggesting device companies work toward the optimal clinical trial design and others suggesting cultural and understanding of clinical trial design be reformed. Recommendations also include the consideration that long term data is crucial to understand the device, safety and effectiveness, and can provide insight into new considerations and uses for the device [7].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Over 43% of these studies did not use any comparator and enrolled a median number of patients of 241. The median duration of primary effectiveness end point follow-up was 3 months 8 .…”
mentioning
confidence: 99%